Primary Health Care in the rural context: the nurses' view - Arleusson Ricarte de Oliveira; Yanna Gomes de Sousa; Doane Martins da Silva; Jairo Porto Alves; Ítalo Vinícius Albuquerque Diniz; Soraya Maria de Medeiros; Claudia Santos Martiniano; Marília Alves (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To analyze the view of nurses from the Family Health Strategy on the health care of rural populations. Method: A qualitative and exploratory research conducted with eleven nurses working in rural areas, conducted from January to March 2017, in Campina Grande-PB. Data was collected through semi-structured interviews and analyzed by the Content Analysis technique. Results: Nurses associate the health context of the rural population with the living conditions of the community, with the lack of access to health services, and with the peculiarities of work resulting from this context. The satisfaction of rural PHC nurses is associated with professional identification and bond with the population. Conclusions: Nurses perceive the particularities that involve the rural context requiring differentiated health care that positively impacts their work.